Biochemical composition and genetic response of green microalgae (Chlorophyta) to the changing environmental conditions along the continental gradients - Wan Omar, Wan Maznah (Universiti Sains Malaysia, 2017)
The seasonal of polar microalgae is mainly controlled by abiotic factors and the microalge growth during summer is controlled by the intensity of available light after the dark polar winter.This study was set up to determine the biochemical responses during growth phases of the Chlorophyta under different environmental conditions.